2017
DOI: 10.3390/genes8100259
|View full text |Cite
|
Sign up to set email alerts
|

Novel EDA or EDAR Mutations Identified in Patients with X-Linked Hypohidrotic Ectodermal Dysplasia or Non-Syndromic Tooth Agenesis

Abstract: Both X-linked hypohidrotic ectodermal dysplasia (XLHED) and non-syndromic tooth agenesis (NSTA) result in symptoms of congenital tooth loss. This study investigated genetic causes in two families with XLHED and four families with NSTA. We screened for mutations of WNT10A, EDA, EDAR, EDARADD, PAX9, MSX1, AXIN2, LRP6, and WNT10B through Sanger sequencing. Whole exome sequencing was performed for the proband of NSTA Family 4. Novel mutation c.1051G>T (p.Val351Phe) and the known mutation c.467G>A (p.Arg156His) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…This mutation found in this study has not been reported in the databases (https://www.ncbi.nlm.nih.gov/clinvar, http://www.hgmd.cf.ac.uk/ac/index.php). The Ectodysplasin‐A protein encoded by EDA gene consists of 391 amino acids and contains 3 structural domains including N‐terminal intracellular domain (1‐41 amino acids), transmembrane domain (42‐62 amino acids), and C‐terminal extracellular domain (63‐391 amino acids). In this family, the c.302_303delCC [p.Pro101HisfsX11] mutation in the proband's EDA gene induced EDA gene frame shift mutation which led to early termination of EDA gene translation because there was a termination codon TAA at the 11th codon behind the mutational site, so only 110 amino acids were translated and the 101‐110 amino acids were also mismatched.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation found in this study has not been reported in the databases (https://www.ncbi.nlm.nih.gov/clinvar, http://www.hgmd.cf.ac.uk/ac/index.php). The Ectodysplasin‐A protein encoded by EDA gene consists of 391 amino acids and contains 3 structural domains including N‐terminal intracellular domain (1‐41 amino acids), transmembrane domain (42‐62 amino acids), and C‐terminal extracellular domain (63‐391 amino acids). In this family, the c.302_303delCC [p.Pro101HisfsX11] mutation in the proband's EDA gene induced EDA gene frame shift mutation which led to early termination of EDA gene translation because there was a termination codon TAA at the 11th codon behind the mutational site, so only 110 amino acids were translated and the 101‐110 amino acids were also mismatched.…”
Section: Discussionmentioning
confidence: 99%
“…The index patient DNA was then subjected to full gene sequencing of the EDAR gene, which is associated with autosomal recessive ectodermal dysplasia, type 10B, and was found to carry the homozygous variant c.73C > T, p.Arg25Ter () in the EDAR gene. The EDAR:c.73C > T variant was reported previously in a 6‐year‐old female patient, albeit in heterozygous form and associated with autosomal dominant HED, type 10A …”
Section: Case Reportmentioning
confidence: 59%
“…This is predicted to cause premature truncation of the EDAR protein and result in the complete deletion of the transmembrane and binding domains which are critical to the EDAR protein's function as a soluble ligand ectodysplasin A receptor and its signaling activity, respectively. The complete loss of protein function due to the c.73C > T mutation and the consequent effect on gene dosage is a likely explanation for why our patient with the homozygous form of this mutation exhibits a more severe clinical presentation than the previously reported patient who presented with tooth agenesis as its major clinical presentation attributed to the heterozygous form of the c.73C > T mutation …”
Section: Case Reportmentioning
confidence: 63%
See 2 more Smart Citations